ANALISIS KADAR BESI DAN MANGAN DALAM LIMBAH INDUSTRI DENGAN ICP-AES SEBELUM DIDEGRADASI DENGAN REAKTOR FOTOKATALITIK FILM TITANIA MENJADI AIR BERSIH - Gusfiyesi Gusfiyesi; Suci Nurjanah; Iwan Mulyawan (JURNAL ILMIAH TEKNOLOGI INDSUTRI (SAINTI), 2019)
The development of titania photocatalytic reactors has been carried out as a solution for processing peat water into clean water that meets the Clean Water Quality Standard requirements. In this study the titania photocatalytic reactor will be used to degrade heavy metals iron (Fe) and manganese (Mn) in industrial wastewater in Batam City. For the initial stage, the wastewater to be degraded is wastewater from six industries, each of which has treated stage. Iron and manganese levels in waste water outlets are determined by the Inductively Coupled Plasma-Atomic Emission Spectroscopy (ICP-AES) device. The results of the analysis found iron and manganese content of 0.0017 ppm and 0.0023 ppm respectively. These results indicate that the processing of industrial waste in each company has been able to eliminate the content of heavy metals iron and manganese and has fulfilled the Regulation of the Minister of Environment No. 5 of 2014 Appendix 47. APHA 3120 B Method: 2012. However, these results have not optimally disappeared heavy metals and besides that the waste treatment process still leaves new waste and uses a lot of chemicals. This research will be continued to remove heavy metals in the industrial wastes with the titania photocatalytic reactor.